Is performance driven by industry‐ or firm‐specific factors? A reply to McNamara, Aime, and Vaaler - Hawawini, Gabriel; Subramanian, Venkat R.; Verdin, Paul (Strategic Management Journal, 2005)
Abstract We revisit the questions of identification of outlying firms within industries and their impact on the relative importance of firm‐ and industry‐specific factors for firm performance. In response to McNamara, Aime and Valler (2005), we argue that the key results in Hawawini, Subramnian and Verdin (2003) are insensitive to the varying methods used to identify firm outliers. Further, we argue that conducting tests on industry outliers are inconsistent to what is indicated by theory and past empirical results on the relative importance of firm and industry effects to firm performance. Firm effects may matter most for outperforming and underpeforming firms, while industry effects may be at least as important to firms ‘stuck in the middle’. Copyright © 2005 John Wiley & Sons, Ltd.